ANALISIS RGEC DALAM MENILAI TINGKAT KESEHATAN BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA - Keytimu, Brian Davisco; M. Khoir (SCIENTIA JOURNAL, 2022)
In the banking sector, it is necessary to encourage new regulations. Products and servicesinnovations, as well as banking activite this was not matching by the application ofadequate risk management can cause very basic problems for banks so that banks needto increasing the effectivenes of the implementations of risk managements and goodscorporate governances, which aims to enable banks to identified problems early and takeaction. further appropriate and faster repairs so that banks are more resilients in the facesof crises. Banking is the main pillar in building the economic and financial system inIndonesia. This happens because banks have a role as an intermediary institution, whichmeans that banks are institutions that channel funds back from parties whose havingexcess funds to those who need funds, thus making banks a supporting unit in investmentand business capital for productive activities. This study aims to find out how thesoundness of commercial banks listed on the Indonesia Stock Exchange in 2017–2019 isseen from the whole by considering aspects of Risk Profile, Good Corporate Governance,Earning and Capital with 17 samples of commercial banks included in the criteria of thisstudy. The results of this study indicate that in terms of NPL, GCG, ROA, and CAR, thesoundness of commercial banks listed on the Indonesia Stock Exchange is healthy.